Investigating post-harvest insect-microbe interactions and their ramifications for global food quality, human health, and insect behavior - Ponce, Marco A. (Kansas State University, 2023)
Microbes are ubiquitous and play important ecological roles. While research has largely focused on arthropods and microbes separately, less attention has been given to their interactions in the post-harvest supply chain. As a result, my aims focused on S. oryzae and L. serricorne and were to 1) evaluate the vectoring capacity of both species for microbes across time, 2) elucidate the behavioral response of each species to microbially mediated volatile emissions in grain, and 3) determine how foraging preferences affect development and fitness among habitats of different quality by each species. To assess the vectoring capacity, both species originated from individuals placed immediately in a novel food patch, or given 24–72 h in a sterilized environment prior. Vectored microbes were imaged after 3–5 d. Increasing dispersal time resulted in multiple-fold reductions in microbial growth by L. serricorne, but not S. oryzae. This was likely attributable to differences in baseline mobility by each species. In addition, we identified 14 taxa and nine genera. Over half of the samples were from Aspergillus spp. Our data suggests that there is a more persistent risk of microbial contamination by S. oryzae than by L. serricorne. In elucidating the behavioral response of S. oryzae to microbial volatiles, two stages (sexual and asexual) of A. flavus were inoculated onto wheat and compared to uninoculated, or UV- sterilized wheat. Using headspace collection coupled with GC-MS, the sexual life stage of A. flavus had the most unique emissions of microbial volatiles. This translated to a higher interaction with kernels containing the A. flavus sexual life stage by S. oryzae in comparison to the asexual life stage. Grain volatiles were more important for attraction at longer distances. In another set of trials, wheat was inoculated with either Fusarium verticillioides or A. flavus and compared to uninoculated grain or UV-sterilized grain. Headspace collection revealed that the Fusarium- and A. flavus-inoculated grain produced significantly different volatiles compared to sanitized grain or the positive control, which translated to changes in close-range foraging by L. serricorne, with a greater frequency of entering and spending time A. flavus-inoculated kernels compared to other treatments. Microbial volatiles were found to be attractive to L. serricorne at longer distances in pitfall traps. Overall, this suggests that microbial volatiles are important for close- and long-range orientation of L. serricorne. To determine how foraging preferences affected fitness, comparisons between habitats inoculated with A. flavus, uncontaminated, or autoclaved in surrogate food patches after 3 d of foraging by S. oryzae and L. serricorne were performed. Insects were released into the dispersal apparatus with habitats located at opposite ends. Our study found that microbes modulated the preference and progeny production of L. serricorne, which dispersed to the uninfested habitats, while S. oryzae showed a preference to reproduce and dispersed to habitats inoculated with A. flavus. In addition, S. oryzae produced progeny that were significantly larger in grain uncontaminated with A. flavus, compared to progeny produced in microbially rich environments. My data suggests that microbial contamination modulates fitness and development.
Keywords: Microbial ecology; Stored products; Rice weevil; Cigarette beetle; Insect-microbe interactions